Hyperparathyroidism-jaw tumor syndrome in Roma families from Portugal is due to a founder mutation of the HRPT2 gene. - Cavaco, B; Guerra, L; Bradley, K; Carvalho, D; Harding, B; Oliveira, A; Santos, M; Sobrinho, L; Thakker, R; Leite, V (2004)
The hyperparathyroidism-jaw tumor (HPT-JT) syndrome is an autosomal dominant disorder characterized by the occurrence of parathyroid tumors and ossifying jaw fibromas. The gene causing HPT-JT, HRPT2, is located on chromosome 1q31.2 and consists of 17 exons that encode a 531-amino acid protein, designated parafibromin. We recently identified six Roma families in Portugal with 56 members (11 affected and 45 asymptomatic), who had the HPT-JT syndrome. We postulated that they may have a common ancestor and that the HPT-JT syndrome may be due to a mutation of the HRPT2 gene. Haplotype analysis using 14 chromosome 1q24-q32 polymorphic markers showed that the 11 affected individuals shared a common haplotype defined by seven markers that spanned an approximately 12.5-cM region, flanked centromerically by D1S202 and telomerically by D1S306. DNA sequence analysis identified a 2-bp (TG or GT) frameshift deletion in exon 8, which predicts a truncated parafibromin protein, in all 11 affected individuals. This mutation was also found in 19 unaffected individuals (age range, 12-74 yr) who shared the affected haplotype, suggesting a low age-related penetrance for HPT-JT in these families. Thus, the HPT-JT syndrome in six Roma families from Portugal is due to a novel founder mutation in the HRPT2 gene.